Development of engineering solutions for subsea interventions in the oil and gas industry with the aid of design thinking methodology - Fernandes, Pedro Gall; Bella, Ricardo Luiz Fernandes (Brazilian Journal of Production Engineering, 2022)
The variation of the price of the oil barrel in the global market increases the competitiveness of the oil and gas companies in the exploration and production activities. The improvement on the customer service is essential for the survival of the service providers due to the increase of competition in recent years. In this context, the application of the design thinking methodology has an essential role in the development of solutions for subsea interventions in this industry, since meeting the lead time and customer needs are fundamental in order to not have an interruption in the oil production. The objective of this study is to analyze how design thinking, associated with methods of product development as design for manufacturing (DFM) and design for assembly (DFA), can be applied in the systems engineering process of a multinational company of the oil and gas industry to enhance results during the execution of development projects. Design thinking is inserted in the soft design science research methodological framework to build a solution to reduce the impacts on the challenges found. The results obtained, such as the interaction among the engineering, projects, operations and purchase departments, help in the management of the activities that make up the product development process, aiming at the operations, deadline and cost needs of the end user.